Strategies and Barriers in Clinical Practice Guidelines Implementation - Magdalena Zielińska; Magdalena Damentko; Kinga Dziok-Dmowska; Sylwia Zemlik; Tomasz Hermanowski (Polish Pharmaceutical Society, 2023)
Object of study Clinical practice guidelines are a set of recommendations formulated in a systematic way by a panel of experts in a particular field. Their purpose is to assist the healthcare professionals in making decisions about appropriate health care. Implementation of guidelines is an ongoing challenge in clinical practice. Despite this, there is a lack of reviews summarizing existing evidence on effective guideline implementation strategies and barriers identified in the implementation process. Purpose of the study The purpose of this study was to review existing systematic reviews and scoping reviews on clinical practice guideline implementation methods, barriers identified in the guideline implementation, and ways to overcome them. Material and methods A systematic literature search was conducted in the PubMed database looking for systematic reviews and scoping reviews that analyzed strategies for implementing clinical practice guidelines or barriers identified in the implementation process. The search included reviews published in English between January 2016 and March 2020. The quality of the included systematic reviews was assessed with the AMSTAR 2 tool. Results The systematic literature review identified 138 articles, of which 6 met the inclusion criteria. Four publications were related to the implementation of clinical practice guidelines while two were related to barriers identified in the guideline implementation process. The clinical practice guideline implementation tools used were assigned to appropriate categories from the EPOC Taxonomy. Our review analyzed guideline implementation strategies that included both multiple and single technique interventions. The effectiveness of single-technique interventions tended to produce equally good results as multiple techniques interventions. The most frequently used tools were educational meetings, audits and feedback. Analysis of the included studies showed that passive distribution of educational materials had short-term and small effects, while the greatest results were observed in approaches that included active participation of intervention recipients in the education process. The introduction of guideline implementation tools allowed for more effective use of the guidelines. We also identified three main categories of barriers, including: personal factors (knowledge, attitude), guideline-related factors, and external factors. The most common barriers related to personal factors were lack of knowledge about the guidelines and lack of the feeling of effectiveness of their application. In terms of guideline-related factors, the main barriers were lack of evidence on the effectiveness of guideline use and the level of complexity in using guidelines in practice. The most common external factors were lack of time and excessive workload. Proposed solutions to the identified barriers included, in terms of personal factors, increasing health professionals' knowledge of guidelines. Access to good quality guidelines that will be simple to implement in practice for guideline-related factors, and better organization of facility work in terms of external factors were additional proposed solutions. Conclusions This study is the first secondary literature review to provide an overview of clinical guideline implementation strategies, barriers identified in the implementation process and methods to overcome them. The use of clinical guidelines ensures both high quality treatment and reduces unnecessary costs, therefore proper use of guidelines is very important. Unfortunately, without adequate support, health professionals are not able to analyze all available guidelines and, as a result, guidelines are often applied carelessly or not used at all. Analysis of the research on the area where implementation is planned is essential for the development of effective implementation methods, enabling the identification of potential barriers to implementation and the optimal adaptation of the implementation strategy to the specific area.